Paradigma Pendidikan Islam Kontemporer: Reinterpretasi Tujuan, Kurikulum, dan Relevansi Sosial - Dayusman, Edo Alvizar; Nazaruddin, Nazaruddin (Ahdāf: Jurnal Pendidikan Agama Islam, 2025)
Islamic education in Indonesia is currently facing global dynamics that demand a reinterpretation of its paradigm to remain relevant, moderate, and competitive. The traditional paradigm, which tends to create a dichotomy between religious sciences and general knowledge, needs to be reintegrated into a holistic and transformative educational framework that is firmly rooted in transcendent values. This study employs a qualitative approach through library research. Data were collected from recent literature, including books, journal articles, and research reports, that discuss the development of Islamic education, curriculum, and pedagogical transformation. The analysis was conducted descriptively and comparatively to examine the principles, values, and strategies of implementing Islamic education in the contemporary era. The findings highlight five key components of the reinterpretation of Islamic education: educational objectives, curriculum, social relevance, pedagogical approaches, and transcendent values. Table 1 presents a summary of the principles and their practical implications, while Figure 1 illustrates the interconnection of these components, positioning transcendent values as the foundational element. This model underscores the importance of integrating religious sciences with science and technology, strengthening the role of teachers, utilizing digital technology, and instilling social justice and ecological awareness. Consequently, Islamic educational institutions can play a strategic role in nurturing a Muslim generation that is spiritually grounded, globally competitive, and capable of addressing contemporary challenges without losing its divine orientation